Mac OS X Snow Leopard for dummies - LeVitus, Bob (--For dummies., 2009)
Features information on the new features and functions of the operating system, along with instruction in how to customize the Dashboard, navigate the Finder, work with the Dock, access the Internet, use iTunes, automate tasks, network, and troubleshoot Mac OS X.